Distributed storage systems and how they handle data consistency and reliability - Aikins, Mark Valentine (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
This paper examines the difficulties and solutions associated with data consistency and reliability in distributed storage systems. Distributed storage systems are necessary for managing data in distributed computing environments but ensuring data consistency and reliability can be challenging. The paper examined various consistency models, such as eventual consistency, strong consistency, and conflict-free replicated data types (CRDTs), as well as techniques for maintaining data reliability, such as replication, erasure coding, and versioning, in a comprehensive literature review. The trend analysis reveals significant advancements in the field, with distributed storage systems continuously improving their ability to balance consistency, latency, and availability tradeoffs. The discussion section of the paper examined the implications of these findings for the design and implementation of distributed storage systems and identifies areas for future research. Examining the impact of emerging technologies such as non-volatile memory on the design of distributed storage systems. The findings provide researchers, practitioners, and system designers working with distributed storage systems and related technologies with valuable insights to advance knowledge in this vital field and develop innovative solutions to meet the rising demands of distributed computing environments.